International marriage migration from Thailand to India: The socio-cultural and religious intermediary in the digital era - Sricahmpa, Sophana (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This qualitative study examines the factors driving the international marriage migration of Thai women to Indian men in the digital age, focusing on how socio-cultural and religious themes are expressed through their YouTube channels and Facebook pages. Methods The research uses a desktop methodology to analyze secondary data, including publicly available videos, posts, comments, and interactions from six selected YouTube channels, each boasting over 100,000 views and active user communities relevant to the topic. Data collection occurred from September to November 2024. The study integrates concepts from globalization, Robert Sternberg’s Triangle Theory of Love, intercultural communication, identity, and diaspora to dissect these dynamics by content analysis. Key findings include the stages of meeting and falling in love, the adaptation process to new family environments, and content produced on social media addressing themes like food culture, religious practices, cultural values, and child-rearing methods. The audience's reflections on these topics were also analyzed. Finding: Although India's population of Thai wives is relatively small, their YouTube and social media platforms have attracted international attention. This visibility can foster greater socio-cultural and religious understanding between India and Thailand, promoting interconnectedness and cooperation in the region. If the Thai embassy and consulates in India were to facilitate a network for these Thai wives, they could effectively champion “Thainess” within the context of “Indianness.” As “civilian ambassadors,” these women could enhance cultural diplomacy between the two nations, contributing to stronger ties and mutual respect. Conclusion: No studies have investigated Thai wives in India functioning as YouTubers. This research underscores the meaningful and authentic socio-cultural and religious perspectives disseminated by these women through digital channels, perspectives largely unacknowledged within the Thai context.